From UNFCCC rules to domestic delivery: An institutional economics explanation of Indonesia’s commitment and implementation gap in emission reduction - Amellya Yunita Syari; Husyaimiah Syifahani; Nuraisyah Jamar; Muh Firmansyah; Wirawan Firman Nurcahya (Journal of Law, Administration, and Social Science, 2026)
This study examines how UNFCCC-based climate governance, particularly the Paris Agreement’s pledge and review logic and the Enhanced Transparency Framework (ETF), shapes Indonesia’s mitigation commitments and explains the persistence of the commitment and implementation gap. Using a theory informed documentary analysis grounded in New Institutional Economics, Transaction Cost Economics, and polycentric governance, the study synthesizes authoritative legal and policy documents alongside credible institutional reports. The findings show that UNFCCC influence operates mainly through domestic credibility producing mechanisms, especially Measurement, Reporting and Verification (MRV) and registry routines, coordination mandates, and finance governance. Indonesia’s delivery gap is concentrated in cross sector regulatory coherence, clean energy implementability within a fossil dominant energy structure, and climate finance governance. Climate finance remains the binding constraint, as investment needs substantially exceed current public coverage and tracked climate aligned flows. The paper argues that Paris effectiveness ultimately depends on domestic governance capacity, particularly regulatory harmonization, implementable renewable deployment, stronger finance governance, and subnational MRV.